THE REALIZATION OF EXPERIENTIAL MEANINGS IN STUDENTS’ WRITING OF RECOUNTS (English Education Journal, 2015)
The aims of the study are to explain the experiential meanings of participants’ element realized in the students’ recounts, to explain the experiential meanings of processes’ element realized in the students’ recounts, and to explain the experiential meanings of circumstances’ element realized in the students’ recounts. The study used is a descriptive qualitative method of discourse analysis. The data were taken from 20 students’ recounts of Writing 4 at English Education Study Program of Unissula. The unit of analysis was a clause. The result of the study showed that the dominant element of experiential meanings was participants’ element (46.5%). The participants’ elements realized by the nominal group with the dominant participants’ types in students’ recounts are actor 19.8 % and goal 14.5 %. The processes’ elements realized by the verbal group with the dominant process are material process in 43.6 %. The circumstances’ elements realized by prepositional phrase, adverbial group, and nominal group with the dominant participants are place circumstance 43.5% and time circumstance 23.7 %.  It can be concluded that the experiential meanings in students’ recounts are realized by the specific participants of actor and goal, material process and circumstances of place and time.